(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
You wake up on a Saturday morning with three hours free. You could go to the gym, call a friend you have not spoken to in months, work on a side project, or catch up on sleep. You pick one. Without even opening an economics textbook, you have just done something profoundly analytical: you have allocated a scarce resource, time, and in doing so, you have silently paid a price for every option you did not take. That silent price has a name. Economists call it opportunity cost, and it is arguably the single most underappreciated concept in everyday life. It shows up when you decide whether to go to college or start working, whether to cook at home or order delivery, whether a government should fund schools or hospitals. In every case, choosing one path means accepting the cost of the path you walked away from.